Morphology, ultrastructure and phylogeny of Auricula weizhouensis sp. nov. (Bacillariophyceae) from the South China Sea. Issue 5 (3rd September 2022) - Zeng, Yulan; Hemed, Ali Masoud; Wang, Pengbin; Gao, Yahui; Lu, Douding; Dai, Xinfeng
ABSTRACT: A new marine diatom species, Auricula weizhouensis sp. nov ., was isolated from Weizhou Island, Guangxi, China, and the morphology was examined in detail. The frustule was symmetrical and quadrate, with four rounded angles. The valve was longitudinally reniform. The vegetative cells of A. weizhouensis were 28.9–35.0 μm in length and 22.2–28.9 μm in width. The mature cingulum was composed of five to six open bands. A large plate-like chloroplast was observed on the ventral side of the girdle. There were 5–7 poroids per 1 μm in a row along the median line. The number of radiate and biforked striae was 15–19 per 10 μm on the ventral margin and 21–31 per 10 μm on the dorsal margin. Striae were biseriate with two rows of areolae (12–14 areolae per 1 μm). Both sides of the double-sigmoid raphe canal had a longitudinal costa. Approximately 21–31 fibulae per 10 μm were arrayed in a row on each longitudinal costa. More importantly, A. weizhouensis and Auricula densestriata could be distinguished from other Auricula species by their characteristic concave ventral margin, and the ventral margin of A. weizhouensis was approximately straight in the middle, whereas that of A. densestriata was inflected. In addition, molecular data from partial SSU rDNA sequences showed that A. weizhouensis (strain WZ-1704-E8) belonged to the genus Auricula, with Auricula complexa (KX120684) as the nearest neighbour (4.58% p -distance). Therefore, both morphological and phylogenetic analyses supported A. weizhouensis as a new species.